Embedded components design strategy framework for fused deposition modeling system - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Sharum, Mohd Afiq; Ismail, Shafinaz (IOP Publishing Ltd, 2024)
This paper proposed a framework for 3D printing of embedded objects specifically for the Fused Deposition Modeling (FDM)system. The main problem revolves around the difficulty of the additive manufacturing process to fully manufacture a product that can be used immediately after the printing process, thus creating the need for embedded component design to be utilized in the process. The framework was utilized to reduce components and assemblies to improve product design. To ensure environmental sustainability, the framework emphasizes materials used to make recyclable items. Design Process Flow, Design Knowledge, Key Enabling Technologies, and Design Application were used to create a four-layered design framework to tackle embedded product design challenges. The framework’s robustness and effectiveness were compared using three case studies: electric shaver, remote control and nintendo switch. The framework proposed a blade-interchangeable product for the electric shaver. In the second case study (remote control) the cover’s flexibility with similar sizes makes it reusable. In the third case study (nintendo switch), every part is interchangeable with numerous styles and designs, allowing the user to autonomously change to the desired pattern without external support. With its various features, the framework shows potential in reducing development time, cost, and resources to aid the embedded component design strategy and printing for the FDM process.